Implementasi Jurnalisme Era Baru dalam Konten Video Medcom.Id - Afalita Intan Givari; Melin Meliyani; Lis Ariani Purba (Syntax Idea, 1957)
The purpose of this study was to find out how Medcom.id's understanding of New Era Journalism was applied in the Video Content Division. This study uses The Theory of 8 functions of new era journalism by Bill Kovach and Tom Rosenstiel, as it’s primary theory. With qualitative interview method with internal staff of Medcom.id to find out the steps taken to implement the new era of journalism theory. The results showed that Medcom successfully implemented six of the eight functions of journalism in the new era. Two functions that have not been successfully implemented are the witnessing function and the intelligent aggregator function.